Effect of Ticagrelor Versus Clopidogrel After Off‐Pump Coronary Artery Bypass Grafting on Postoperative Atrial Fibrillation: A Cohort Study - Qin Jiang; Keli Huang; Lixue Yin; Hong Kong; Zhenglin Yang; Shengshou Hu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to explore the effect of a P2Y12 inhibitor regimen on the occurrence of postoperative atrial fibrillation (POAF) after off‐pump coronary artery bypass graft surgery in carriers with the cytochrome P450 family 2 subfamily C member19 loss‐of‐function allele. Methods and Results From May 2019 to November 2023, patients containing the cytochrome P450 family 2 subfamily C member19*2 or *3 allele undergoing elective first‐time off‐pump coronary artery bypass graft surgery including aspirin 100 mg/d and ticagrelor 180 mg/d (AT group; n=95) versus clopidogrel 75 mg/d (aspirin and clopidogrel group; n=95) were prospectively followed. The primary end point was the cumulative incidence of POAF in a week. The secondary end points were POAF burden, platelet aggregability, systemic immune‐inflammation index and heart rate variability. The incidence of POAF was 21.1% in the AT group versus 41.1% in the aspirin and clopidogrel group (hazard ratio, 0.46 [95% CI, 0.27–0.76]; P=0.003). POAF burden, ADP‐induced platelet aggregation and systemic immune‐inflammation index was notably lower in the AT group than the aspirin and clopidogrel group. Heart rate variability data showed an increase in both high‐frequency and SD of normal‐to‐normal RR intervals in the AT group with a decreased low‐frequency/high‐frequency ratio, suggesting that the sympathetic/parasympathetic activation was balanced. Conclusions In patients carrying the cytochrome P450 family 2 subfamily C member19 loss‐of‐function allele, an AT regimen after off‐pump coronary artery bypass grafting was associated with a lower incidence of POAF, paralleled by lower atrial fibrillation burden, ADP‐induced platelet aggregation, lower systemic immune‐inflammation index reaction, and a balanced automatic nerve system compared with an aspirin and clopidogrel regimen. Inhibiting the systemic immune‐inflammation response and sustaining automatic nerve balance may underlie the therapeutic effect of POAF by a potent antiplatelet combination.